Tinjauan Hukum Pendanaan Pelaku Usaha Mikro, Kecil, dan Menengah Sebagai Bantuan Modal Kerja pada Masa Pandemi Covid-19 di Kota Tangerang Berdasarkan Peraturan Menteri Koperasi, Usaha Kecil, dan Menengah Republik Indonesia Nomor 6 Tahun 2020 - Fauziatul ula; Nurikah Nurikah (Yustisia Tirtayasa: Jurnal Tugas Akhir, 2021)
The 2019 Corona Virus Disease pandemic poses a threat to Micro, Small, and Medium Enterprises, as seen from the decline in turnover to no income and causing bankruptcy. Government policies in dealing with the economic impact during the 2019 Corona Virus Disease pandemic, the government gives priority to support for Micro Enterprises with large budget allocations. Therefore, this study discusses how the legal aspects of funding micro, small, and medium enterprises as working capital assistance during the Corona Virus Disease 2019 pandemic in Tangerang City based on the Regulation of the Minister of Cooperatives, Small and Medium Enterprises Number 6 of 2020? from the implementation of micro, small and medium business capital assistance in the Tangerang City area to the sustainability of Micro, Small, and Medium Enterprises?. The research method used in the preparation of this legal writing is empirical juridical research, namely research that sees the law as a rule in society to be obeyed, with analytical descriptive specifications that discuss working capital assistance during the Corona Virus Disease 2019 pandemic in Tangerang City which is sourced from data The primary sources are legislation, books, legal science journals, and other library materials which were analyzed qualitatively. The results of this study, that the Government implements policies through the Direct Assistance Program for Micro Enterprises with the aim of strengthening the business of Micro, Small, and Medium Enterprises. The existence of such capital assistance has a positive impact on the economy in the community, thereby increasing employment opportunities.